Allanite Petrochronology in Fresh and Retrogressed Garnet–Biotite Metapelites from the Longmen Shan (Eastern Tibet). (5th December 2018) - Airaghi, Laura; Janots, Emilie; Lanari, Pierre; de Sigoyer, Julia; Magnin, Valérie
Abstract: Linking the timing of allanite growth to metamorphic conditions in metapelites is particularly challenging because of the large variety of allanite textures and chemical compositions. This study focuses on five garnet–biotite metapelites retrogressed to different extents, from the internal domain of the Longmen Shan (eastern Tibet) from which few petrochronological data documenting the metamorphic ages are available. Microstructural observations were combined with whole-rock compositions, detailed mineral characterization, phase equilibria modelling, and in situ U–Th/Pb allanite dating to gain insights into the allanite reactivity relative to other rock-forming minerals. All samples experienced similar peak temperatures of 560–600°C. Allanite is the main rare earth element (REE)-bearing accessory mineral but it exhibits different textures, such as epidote rims with distinct REE contents as well as late inclusion-like dissolution features. Garnet is, along with allanite, critical to reconstruct the REE budget of these rocks. In the two samples where allanite is observed as inclusions in garnet, garnet shows no textural zoning and a low Y content (<90 ppm). This is attributed to early Y fractionation in allanite and epidote rims with no further equilibration with garnet. This allanite is therefore pre-garnet ( T < 520°C). In the sample where allanite is observed only in the matrix, both garnet and allanite–epidote rims exhibit more complex textural and compositional zoning, with a higher Y content in garnet. The Y incorporation in garnet is attributed to a series of reactions involving allanite, interpreted as syn- to post-garnet growth ( T > 520°C). This relative chronology is confirmed by in situ U–Th/Pb allanite dating: pre-garnet allanite shows ages of c. 200 Ma, whereas syn- to post-garnet allanite has ages of c. 180 Ma. The timing of allanite appearance strongly correlates with the biotite-in reaction predicted by the models and observed in microstructures. In the two samples collected close to the major Wenchuan Shear Zone—deformed up to mylonitization and retrogressed under greenschist-facies conditions (3–4 ± 1 kbar, 350–400°C)—allanite still preserves the peak metamorphic ages ( c. 200 and c. 180 Ma). Allanite and its epidote rims, however, are fragmented and partly replaced by a retrograde assemblage of Qz + Pb-depleted (<100 ppm) monazite, providing an age <90–100 Ma. Our results allow different metamorphic stages for the studied transect in the central Longmen Shan to be refined: a prograde path at c. 200 Ma, a thermal relaxation and exhumation from c. 180 Ma, and a late greenschist overprint. This study also shows that when allanite is the principal phase in a mineral assemblage datable by U–Th/Pb, detailed observations of allanite textures may be highly informative in constraining the timing of its growth relative to other major mineral phases.